2012
DOI: 10.1007/s10823-012-9174-1
|View full text |Cite
|
Sign up to set email alerts
|

Gogo Care and Protection of Vulnerable Children in Rural Malawi: Changing Responsibilities, Capacity to Provide, and Implications for well-being in the Era of HIV and AIDS

Abstract: The role of older women in the care and protection of vulnerable children in sub-Saharan Africa may be changing given increasing rates of orphanhood due to AIDS. Concern regarding their capacity to provide for children and implications for their health and well-being dominate the literature. However, studies have not yet examined the situation of older caregivers in comparison to their younger counterparts over time. In this study, panel data on 1,219 caregivers in rural Malawi between 2007 and 2009 is complem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 38 publications
4
8
0
Order By: Relevance
“…We found that a number of older carers, whatever their health status, suffered from stress and anxiety in their role which affected how they looked after the child. This is consistent with other research which has shown that carers of orphaned children, regardless of their age, suffer poor general health and functioning and increased levels of depression, anxiety, and post-traumatic stress [ 15 , 31 ]. On the issue of food scarcity we observe that this is a seasonal problem, although occasionally there are years of more extensive shortages.…”
Section: Discussionsupporting
confidence: 92%
“…We found that a number of older carers, whatever their health status, suffered from stress and anxiety in their role which affected how they looked after the child. This is consistent with other research which has shown that carers of orphaned children, regardless of their age, suffer poor general health and functioning and increased levels of depression, anxiety, and post-traumatic stress [ 15 , 31 ]. On the issue of food scarcity we observe that this is a seasonal problem, although occasionally there are years of more extensive shortages.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, most of these persons were the sole caregivers for their adult children, despite the fact that some of them (12 out of 31) were over 70 years of age. This study confirms the findings of previous studies conducted in sub-Saharan Africa, which indicate that older women are responsible for providing care to their adult children living with HIV/AIDS [11,30].…”
Section: Discussionsupporting
confidence: 91%
“…The elderly carers lacked resources during the care for people with AIDS-related illnesses [ 33 ]. Consistent with other studies, the elderly carers did their best under difficult and trying circumstances to provide physical care and ensure the hygiene of their children [ 20 , 34 ].…”
Section: Discussionsupporting
confidence: 79%